Shunt Infection - Maurice Choux (Brazilian Society for Pediatric Neurosurgery, 2021)
The improvement in the management of hydrocephalus comes from the following: early diagnosis, radiological investigation, better knowledge of mechanisms, quality of material, surgical technique of implantation, less shunt complications (e.g.infections) and alternatives to shunt (e.g. Neuroendoscopy). However, shunt infection does not improve in the last decades, ranging from 3 to 12%. Shunt infection can be classified in: would infection, CSF infection, infected shunt system, abdominal complications (infection). The main agent is Staphylococcus, causing 67%-85% of problems, mainly due to colonization of shunt by skin flora. The majority of cases occur during the first 2 months (85%), late infection is rare. Risk factors to infection are the following: the cause of hydrocephalus, clinical condition and the age of children, operation time of the day, the duration of the shunt operation, the number of persons in OR, shunt material (Antibiotic catheter), presence of previously shunt system, postoperative CSF leak, perioperative antibiotics and economic level of Medical Center. Recommended management of shunt infection: removal of the shunt, insertion of an external drainage (EVD) (always in operation room), change EVD after 15 days, intravenous antibiotics, replacement of ventriculoperitoneal shunt after 3 sterile cultures. The most feared complications of Shunt infection are mortality, morbidity and cost. In conclusion: SHUNT INFECTION IS NOT A FATALITY